Deeds and papers relating to properties in Penang, Batavia, Malacca and Singapore
Papers relating to property at Penang: 1. Letter to Woollacott and Leonard re London Missionary Society and Aitken, Penang, 27 Apr 1872 2. Plan of property formerly belonging to J. Anderson in North Penang. Originally enclosed with Mr Logan's letter of 27 Apr 1870 3. London Missionary Society, Penang property. Letter of authority to Mr Aitken as to payment of purchase money, 18 Jun 1870 4. Description of the London Missionary Society property in Pulo Penang proposed to be sold. Handwritten, n.d. 5. Letter from Joseph Mullens, Foreign Secretary of the London Missionary Society, relating to a petition drawn up by members of the Penang mission and issuing the decision of the directors who think it unwise to maintain property in that field, which they are moving out of. Handwritten copy. 22 Oct 1869 6. A reply to the letter dated 22 Oct 1869 to Joseph Mullens, Foreign Secretary to the London Missionary Society. In this letter it is argued that the sale of the Chapel is unpopular and that the missionaries are too poor to buy it for themselves. 6 Dec 1869 7. Letter from G. Gottlieb to Mr Beighton advising him that it would be a shame to sell the land in Penang on which the Girls' school, Boys' school, Chapel and Mission House are built. Instead he brings to his attention a piece of land previously made as a gift to the LMS, adjoining the original site to be sold. 2 Nov 1868 8. Sir Culling Eardley-Smith and William Alex Hankey to Rev B P Keasbury. Draft Power of Attorney to sell lands situate at Pulo Penang, the property of the London Missionary Society, 25 Feb 1846 9. Resolution of the Board of Directors relating to London Missionary Society Property in Penang, 13 Oct 1845 10. Petition from members of the Missionary Church in Penang sent to the London Missionary Society relating to the sale of their Church. Handwritten original. 9 May 1869 11. Letter from Rev William Ellis to Rev Mullens concerning a letter from A E H Anson, Governor of Penang, regarding property of the London Missionary Society. An extract from the aforesaid letter is enclosed. 3 Jan 1868 12. Copy of Resolutions of the Board of Directors adopted 20 Oct 1868, relating to property in Penang. Handwritten. n.d. 13. Letter from J. Mullens, foreign secretary of the London Missionary Society to Wollacott and Leonard relating to the London Missionary Societies properties in Penang, 15 Dec 1869 14. Letter to Woollacott and Leonard acknowledging the letter sent on the 3rd Dec [1868], 4 Feb 1869 15. Letter to Mr Parsons requesting that a power of attorney be drawn up for the Rev. G. Bausum in Penang so he can sell a small building at that place belonging to the London Missionary Society, 3 Nov 1854 16. Letter from J. Beighton to Woollacott and Leonard relating to the deeds of the property at Penang in their possession, 15 Jul 1868 17. Letter from F. Fox to T. E. Parker reminding him to grant the power of attorney to Mr Bausum, 23 May 1855 18. Letter from Mr Read relating to a letter he had just received from Rev E. Davies saying it will not be possible to meet until the following week, 29 Jan 1846 19. Letter from J. Beighton to Mr Read stating the properties, which make up the London Missionary Societies holdings in Penang. Handwritten original, 19 Dec 1845 20. Letter from F. Fox to E. Parson relating to resolutions in Minutes from a meeting relating to property in Penang, 12 Feb 1846 21. Extract of letter from the late Foreign Secretary Re Dr Tidman to Mr Bausum, Penang, 3 Jul 1856 22. Letter from J. Mullens, Foreign Fecretary to the London Missionary Society to Woollacott and Leonard. Cover letter sent with enclosures including memorial from members of the Penang Mission Chapel with copy of Director's reply to the same, 25 Jan 1870 23. Letter from J. Mullens Foreign Secretary to the London Missionary Society to Woollacott and Leonard relating to the death of Mr J. Logan and the sale of land in George Town, Penang, 15 Dec 1869. Includes small advert for sale of land and buildings. 24. Letter from [? name unreadable] to Woollacott and Leonard regarding London Missionary Society's property at Penang, regarding the delay in releasing the property, 3 Feb 1870 25. Letter from Mactaggart Timmans Co. to Woollacott and Leonard stating that Mr S. Logan went to Penang on the death of his brother J. Logan and that they must contact him to deal with any business, 17 Dec 1869 26. Extract from the minutes of the Directors of the London Missionary Society of the 29 May 1854, that a Power of Attorney be sent to Mr Bausum to enable him to sell the old schoool house in Penang. Handwritten copy. c1854 27. Penlo Penang premises. Receipt for legal documents handed to Mr Read on 1 Sep 1848 28. Draft letter regarding London Missionary Society properties at Penang, 1 Dec 1868 29. Letter to Messrs Woolacott and Leonard, 27 Aug 1869, relating to property in Penang 30. Letter to Mr Parson from London Missionary Society, 13 Jul 1855 31. Extract of a resolution that Mr Hankey's representatives be asked to execute the conveyance of the property in Penang on behalf of the London Missionary Society. Handwritten copy. n.d 32. Letter to Woollacott and Leonard from J. Whitehouse stating that there is no means of checking on the account of Mr Hawthorne's thus it will have to be accepted as it stands. Also mentions how the Chapel in Penang was being used, 23 Jun 1870 33. Letter from Messrs Woolacott and Leonard from J. Mullens, relating to resolutions decreed by the Board, 16 Jun 1870 34. Letter from Mr Whitehouse to Woollacott and Leonard expressing the wishes of the late J. G. Bausum in a letter dated 1 Aug 1846. The wishes include purchasing a parcel of land adjoining the LMS premises, 23 Jun 1870 35. Letter from R. Robinson to Woollacott and Leonard acknowledging receipt of draft for £687.10.7., 19 Oct 1870 36. Letter to Woollacott and Leonard relating to title deeds for Penang Property, 10 Sep 1870 37. Duplicate of 36. 38. Letter from J. Mullens to Woollacott and Leonard acknowledging the receipt of £697. 10. 7 on account of proceeds of the Penang estate, 7 Dec 1870 39. Letter to Woollacott and Leonard requesting a copy of a letter or document of the late Dr. Baanseem in relation to a small piece of land adjoining the London Missionary Society's premises, Penang, 3 Feb 1871 40. Letter from J. Mullens to Woollacott and Leonard relating to London Missionary Society property in Penang, 9 Mar 1871 41. Letter to Woollacott and Leonard stating that their instructions for the sale of property was carried out on the 11th and giving details of the sale, 21 Apr 1870 Title deeds of the ground and adjoining ground of the Missionary Chapel, Penang: 42. Printed map [Penang?] n.d. 43. Bundle of 'Title Deeds of the ground to the westward of and adjoining the ground on which the Missionary Chapel is now erected assigned by John Anderson Esq. to William A. Hankey, the Treasurer to the London Missionary Society and his successors in office in trust for the said Society'. Concerns property north of Battery Lane, George Town, Prince of Wales Island. 30 handwritten items, originals and copies, 1818-1872 44. Four letters relating to property in Penang and construction work; list of Deeds relating to London Missionary Society property in Penang; eleven property deeds for land in Penang. Handwritten copies and originals. 1820-1840 45. Set of title deeds and extracts of resolutions from the Board of Directors relating to property at Batavia and Malacca. Also includes a surveyors map of the land at Malacca. Handwritten originals and copies. 1820-1842 46. Set of property deeds in Dutch and English relating to land at Malacca. Handwritten original with translations. 1 Mar 1821 47. Set of deeds and papers relating to the sale land and property at the Anglo Chinese College in Malacca. Handwritten copies. 1841-1842. Includes instructions for Powers of Attorney to Dr Legge, Rev Samuel Dyer, Rev John Stronach and Mr Medhurst 48. Papers relating to conveyance of property at Singapore between the East India company and Right Rev Hilary Courrezy. Handwritten copy. 1 Aug 1840 49. Set of thirty five documents, including receipts, correspondence and deeds relating to mission land in Singapore, and to Rev C. H. Thomsen's case. Handwritten and printed originals. c1819-1866. [Note that some of these letters are extremely fragile]